Giant lipoma in the hand: A case report - Kim, Kwang Seog (Medicine (Baltimore), 2019)
RATIONALE: Although lipomas are the most common benign form of soft tissue tumor in the body, giant lipomas of the hand, defined as >5 cm in diameter, are extremely rare. PATIENT CONCERNS: A 49-year-old man presented with a soft and fixed lump in the left hypothenar area. The mass was not tender, but it was associated with symptoms of tingling sensation and paresthesia in the left ring and little fingers that had lasted for 4 years. DIAGNOSES: Preoperative image studies revealed an encapsulated and multilobulated mass, which measured 8 cm × 5 cm × 2 cm. Basic histologic examination identified the specimen as a lipoma and further immunohistochemical studies ruled out the possibility of malignancy. INTERVENTIONS: To enable a complete excision of the mass, the palmar digital branch of the ulnar nerve for the little finger passing through the mass was temporarily transected. After complete excision of the mass, the branch was coapted again under microscopy. OUTCOMES: Complete sensory recovery was achieved 6 months after surgery, without any sign of recurrence. LESSONS: Although giant lipomas in the hand can extend to vital components such as neurovascular structures, muscles, and tendons, meticulous en bloc resection can provide excellent results without any complications.